OBJEKTIVITAS IMAJINASI DALAM SENI - Susapto Murdowo (FBS UNY, 2006)
In reality, art structure is dual and relational. A work of art can beviewed as a subjective and objective ‘structure’. Arts always appear ascontinuous acts in imagination. The artists exist in the material world (the worksof art) and in other life experiences. Besides, the objective understanding ofimagination in art is expected to enhance epistemological ways of thinking andunderstanding as a reaction against a tendency towards verbalism of reality andtruth. Finally, it is expected to motivate someone to be wiser, highly consciouswith his willingness to create art works, as well as to build a system or frameworkin the forms of unique and personal expression.Keywords: art structure, objectivity, imagination